Pengaruh Model Pembelajaran Kooperatif Tipe STAD terhadap Pemahaman Konsep Fisika pada Materi Gelombang Bunyi - Nur Isnaniah; Gita Trisnawati; Qathrun Nada Hayati (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2022)
This study aims to determine the effect of the STAD type cooperative learning model on physics learning outcomes of sound wave. This type of research is a literature study using various books and related scientific journals. STAD type cooperative learning model is able to increase student activity during the learning process. This is because students have the opportunity to discuss problems related to the subject matter taught with their groups, then present the results of their discussions, and evaluate their understanding by giving quizzes or questions on worksheets and individual tests. This indirectly leads to the fact that all these processes tend to make students more active in finding concepts and communicating. Therefore, the STAD type cooperative learning model is able to improve students' cognitive, psychomotor, and affective values better.